2010
DOI: 10.1016/j.jembe.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the live market: Recovery of Norway lobsters Nephrops norvegicus (L.) from trawl-capture as assessed by stress-related parameters and nucleotide breakdown

Abstract: Finally, animals in the winter were better able to endure further stresses (an emersion of 1 h while animals were transported to the commercial handling facilities).Therefore, as a code of practice it is advised that trawled N. norvegicus directed to the live trade should be allowed to recover for at least 4-6 h in on-board tanks, and extra care should be taken especially in the summer, if further stresses such as additional emersion are to be applied within the first 24 h after capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
(52 reference statements)
1
27
0
Order By: Relevance
“…Under such a condition, L-lactate, the major anaerobic end-product, has been observed to be elevated in many crustaceans exposed to air, such as lobsters (Vermeer, 1987;Taylor and Waldron, 1997;Lorenzon et al, 2007;Albalat et al, 2010) and crabs (Luquet and Ansaldo, 1997;Durand and Regnault, 1998;Barrento et al, 2011Barrento et al, , 2012Urbina et al, 2013;Simonik and Henry, 2014). This indicates that one defense mechanism for crustaceans against air exposure effects is resorting to anaerobic glycolysis which serves as a means to replenish adenosine triphosphate (ATP) for animals to cope with external stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under such a condition, L-lactate, the major anaerobic end-product, has been observed to be elevated in many crustaceans exposed to air, such as lobsters (Vermeer, 1987;Taylor and Waldron, 1997;Lorenzon et al, 2007;Albalat et al, 2010) and crabs (Luquet and Ansaldo, 1997;Durand and Regnault, 1998;Barrento et al, 2011Barrento et al, , 2012Urbina et al, 2013;Simonik and Henry, 2014). This indicates that one defense mechanism for crustaceans against air exposure effects is resorting to anaerobic glycolysis which serves as a means to replenish adenosine triphosphate (ATP) for animals to cope with external stress.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of ATP and its decomposition products (ADP and AMP) is described by adenylate energy charge (AEC) which indicates the amount of energy available to an organism from the adenylate pool (Wang et al, 2006). This effective indicator has been quoted to reflect the physiological status and health of muscle cells in aquatic animals (Morris and Adamczewska, 2002;Albalat et al, 2010;Ivanina et al, 2013). AEC values are reported to be higher than 0.8 in invertebrates in a suitable environment (Atkinson, 1977;Ivanovici, 1980), while the values lower than 0.5 indicate an irreversible physiological collapse in animals (Sylvestre and Le Gal, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Survival studies on Nephrops have reported variable survival rates following capture, air exposure and transport procedures (Ulmestrand et al, 1998;Campos et al, 2015;Bergmann and Moore 2001;Philp et al, 2015), but if post-catch practices are optimised then relatively high survival rates can be achieved, even after trawling (Lund et al, 2009;Albalat et al, 2010). The condition of such animals can nevertheless vary, especially with season (Lund et al, 2009), and for this reason visual methods to assess their condition are important (Stoner, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is determined by the nature of the capture process used (Wilson et al, 2014) and also by the post-capture handling procedures (Milligan et al, 2009;Raicevich et al, 2011;Leocádio et al, 2012;Lorenzon et al, 2013). Improved practices in trawl fisheries, such as on-board recovery tanks, have made it possible to increase the proportion of trawl-caught crustaceans that can be transported alive successfully (Albalat et al, 2010). However, a number of trawl-caught animals fail to recover, and such animals do not survive subsequent live transportation, which may take 24-72h.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation